Introduzione (ENTHYMEMA, 2017)
Introduzione al numero speciale dedicato alla forma del romanzo di famiglia contemporaneo tra centri e periferie, a cura di Elisabetta Abignente e Emanuele Canzaniello. Il numero presenta i risultati del progetto STAR 2014 Linea 1 dal titolo The family novel. Intergenerational Novels, Family Memoirs, Changing Society in Changing Fiction Forms. New Approaches to the Family Novel in European and American Literature from 1950 to 2010 che si è svolto presso il Dipartimento di Studi Umanistici dell'Università di Napoli Federico II dal 1 settembre 2015 al 30 novembre 2017. Il team di ricerca era composto da Elisabetta Abignente, Francesco Arcidiacono, Emanuele Canzaniello, Francesco de Cristofaro, Karen Haddad, Giovanni Maffei, Matteo Palumbo. Introduction to the special issue on the contemporary family novel between centre and periphery, edited by Elisabetta Abignente and Emanuele Canzaniello. The issue presents the results of the STAR 2014 Linea 1 Project entitled The family novel. Intergenerational Novels, Family Memoirs, Changing Society in Changing Fiction Forms. New Approaches to the Family Novel in European and American Literature from 1950 to 2010, carried out at the Dipartimento di Studi Umanistici dell’Università di Napoli Federico II from September 1, 2015 to November 30, 2017.
Keywords: Romanzo familiare; family novel; Familienroman; borghesia; bourgeoisie